2007
DOI: 10.1016/j.ijid.2006.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of rapid influenza diagnostic testing on antibiotic prescribing patterns in rural Thailand

Abstract: Thai outpatients with ILI are prescribed antibiotics at a frequency approximately twice that reported in the USA. Having access to a rapid influenza test result was associated with a significant decrease in antibiotic prescription. Improved access to rapid influenza testing and expanded physician education may reduce inappropriate antibiotic use and improve patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 25 publications
(35 reference statements)
3
37
0
Order By: Relevance
“…Among patients presenting with ILI to five OPDs, 82% received a prescription for an antibiotic. 6 The OPD environment may help drive the overutilization of antibiotics, as continuity of care and medical records are lacking, and the implementation of techniques such as delayed antibiotic prescriptions is not feasible. 23 We were able to develop simple clinical prediction tools for influenza for both children and adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients presenting with ILI to five OPDs, 82% received a prescription for an antibiotic. 6 The OPD environment may help drive the overutilization of antibiotics, as continuity of care and medical records are lacking, and the implementation of techniques such as delayed antibiotic prescriptions is not feasible. 23 We were able to develop simple clinical prediction tools for influenza for both children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…5 Improving the diagnosis of influenza in such settings is vital for both epidemiologic and clinical purposes, which include measuring disease burden, directing public health measures, reducing unnecessary antibiotic use, and targeting antiviral use. 6 In Sri Lanka, a total of 1,560 hospitalizations due to influenza were reported in the country's Annual Health Bulletin in 2012, but the true burden of influenza is likely greater due to limited laboratory testing. In 2003-2004, influenza accounted for 11% of acute respiratory infections in patients presenting to Colombo North Teaching Hospital in Ragama, located in the more urbanized Western Province.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly access to a prompt influenza test outcome was associated with a significant decrease (73% versus 87%, respectively, p=0.003) in antibiotic prescription and promote rational prescribing. The study finally concluded that wide accessibility user-friendly rapid influenza testing and expanded physician continued education diminishes the irrational antibiotic use, promote prudent use, and progress patient care [74].…”
Section: The Kingdom Of Thailandmentioning
confidence: 98%
“…The major importance of misuse of antimicrobials is the rapid advent of AMDR [76][77][78] and its' consequent disease aftershock [74]. Irrational antibiotic use refers to inappropriate, imprudent and does not comply evidence-based medicine with respect to choosing the drug, dose, interval, duration in the light of appropriate clinical circumstances and/or financial contemplations [79].…”
Section: The Republic Of the Philippinesmentioning
confidence: 99%
“…In European countries, systemic antibiotics are prescribed in greatest volume to ambulatory patients, mostly for respiratory tract infections [33]. Recent studies from Eastern Europe have identified the inappropriate use of antibiotics for viral infections of the respiratory tract and sub-therapeutic dosing as common in both hospital and ambulatory settings (in one published report correct dosing was reported in 38% of outpatient and 74% of medical charts of children with respiratory infections in hospital that were reviewed) [34,35] In Thailand, unnecessary use of antibiotics is seen among both health professionals and the public [36][37][38] One study in a tertiary care hospital revealed that only 7.9% of the upper respiratory tract infections (URIs) in the facility were caused by bacteria [39,40] Despite this, in Thailand most URIs are treated with antibiotics by hospitals, health centers, drug stores and patients themselves [41][42][43][44][45]. Liberal use of antibiotics endangers the health of patients without observable clinical benefits, since it neither reduces the rate of complications nor quickens recovery when the illness is caused by a virus [46,47].…”
Section: The Need For Stewardshipmentioning
confidence: 99%